PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN YANG DI MEDIASI KEPERCAYAAN PELANGGAN (STUDI KASUS PADA WARDAH) - Kholifah Putrikurnia Azhari; Soepatini Soepatini (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to analyze the effect of corporate social responsibility and customer satisfaction on customer loyalty mediated by customer trust (case study in Wardah). This research method is quantitative. The population of this study was Wardah customers. The sample technique used in this study was purposive sampling. The sample size of this study was 168 respondents. The research data used in this study came from primary sources. Data collection techniques with questionnaires. Data processing techniques using Partial Least Square (PLS) with smartPLS program version 3. The result of this study is that Corporate Social Responsibility has a positive and significant effect on Customer Trust. Customer Satisfaction has a positive and significant effect on Customer Trust. Corporate Social Responsibility has a positive and significant effect on Customer Loyalty. Consumer satisfaction has a positive and significant effect on customer loyalty. Customer Trust has a positive and significant effect on Customer Loyalty. Corporate Social Responsibility has a positive and significant effect on Customer Loyalty mediated by Customer Trust. Customer Satisfaction has a positive and significant effect on Customer Loyalty mediated by Customer Trust